Word Formation Patterns of Technological Neologisms in English Digital Media: A Morphological Analysis Based on O’Grady and Guzman - Ahmadi, Yusril; Syamsurijjal; Syahid, Agus (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This study examines the formation of neologisms in English-language digital media, focusing on the technology news platforms TechCrunch and Wired. Using O’Grady & Guzman (1996) morphological framework, this study identifies five main word formation processes: compounding, word blending, derivation, acronyms, and conversion. These processes are analyzed qualitatively through 10 neologisms extracted from both media. TechCrunch and Wired were selected due to their central role in documenting and popularizing technological innovations and terminology. The findings show that derivation and compounding are the most dominant patterns, indicating that morphological creativity in a technology-driven context is highly dependent on simplicity and clarity. These results highlight the dynamic relationship between linguistic innovation and technological development, suggesting that neologisms not only reflect lexical changes but also serve as tools to accommodate emerging digital realities.